MENYAMBUT SEKOLAH RUMAH (HOMESCHOOLING) DALAM SISTEM PENDIDIKAN NASIONAL DI INDONESIA - Harun Al Rasyid (Jurnal Ilmiah Visi, 2007)
Homeschooling practice in Indonesia has just started in 2006. There are many reasons and philosophies in the presence of home schooling, both internally such as family and students, and externally such as educational considerations. In at least, there are three types of homeschooling, they are: (1) homeschooling for pre-school children, (2) homeschooling as the substitution and complementation to formal school and (3) homeschooling as a sustainable education program. As a new category in the formal education practice in Indonesia, the presence of homeschooling should immediately be set up its connectivity model with national education system within its holistic view. It will need a comprehensively conceptual, theoretical, and philosophical consideration being the foundation of homeschooling practice so that homeschooling may run in the normative path of education. In the other hand, there is a necessity for supporting regulations, policies and action plan, which would guarantee the continuity and development of homeschooling in Indonesia. Therefore, homeschooling contributions within national education system may soon be used effectively in the efforts of promoting the intellectual life of the nation.